Pengaruh profitabilitas, leverage, likuiditas terhadap nilai perusahaan (studi empiris pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2019 – 2022) - Siska Yulia Weny (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
Indonesia is currently experiencing rapid progress in the economic field, where many companies compete to dominate the market. Financial statements can consist of profit and loss reports, reports on changes in capital, and statements of financial position. Then using data from financial reports will be analyzed using profitability ratios, liquidity ratios, solvency ratios, activity ratios, and investment ratios. The purpose of this study is to determine the effect of profitability, leverage and liquidity on firm value, to analyze the effect of profitability, leverage and liquidity on firm value. The research method used is quantitative. The results of this study are liquidity, leverage, profitability have an effect on firm value